STUDI PERBANDINGAN OF GENERALIZE COST VESSEL MODA KAPAL KETINTING DENGAN MODA ANGKUTAN KOTA TRAYEK MAHAKAM HILIR-SAMARIDA SEBERANG - Ahmad Syapawi (Politeknik Negeri Sriwijaya, 2013)
River transport was originally a major transportation on Route Mahakam Downstream - Samarinda Seberang, is due to geographical conditions that are linked by the Mahakam river is the one - the only transportation that can be used locals to conduct its activities. At this time the river transport has decreased quite dramatically, is caused by the establishment of the Mahakam Bridge that connects between the Mahakam Downstream - Samarinda Seberang so many are interested to make the overland route with the same objectives as the vessel ketinting the Mahakam Downstream - Samarinda Seberang. The bridge construction with the advantages possessed, enabling service users to switch to using land transport modes are considered a benefit for service users.Research conducted at the time was intended to find solutions to improve transport activity Mahakam river downstream - Samarinda Seberang route. Data is collected using a questionnaire method Stated preference value at the time that also enter the variable characteristics of the respondents and the questionnaire Stated preference generalize based on a scenario which includes the travel costs, travel time and waiting time of vehicles which was distributed to 158 service users moving, the sample using the mode river and land transportation modes .Analysis of the problem done by finding the value of everyone's time to then get the total cost of the service user's overall travel that moves with each - each mode of both modes of the river and overland modes with the same purpose. With the help of spss 15.0 for windows evaluation version available Ratio Binary logit models are used to determine the proportion of service users against the selection mode of river transportation between the ship and freight cars ketinting city, as well as problem solving that is used as an effort to increase the activity mode of the lower river several variables forming generalize cost as travel costs and travel time.